KEEFEKTIFAN PERANGKAT PEMBELAJARAN KOOPERATIF THINK PAIR SQUARE (TPSQ) PADA MATERI KUBUS, BALOK, PRISMA DAN LIMAS - Maryati - (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2015)
This study was an experimental research that began with research development. This study aims to: (1) generating device cooperative learning Think Pair Square (TPSq), (2) describing the effectiveness of cooperative learning Think Pair Square (TPSq). This study uses Four-D models for the development of learning tools that have been modified, which consist; defining, designing, and developing.The learning tools used inthis research are lesson Plan (RPP), Student Worksheet (LKS), and Test of LearningResults (THB). The research instrument used is a learning device validation sheets, observation sheets teachers manage learning, student activity observation sheet and student questionnaire responsessheet. Experimental class treated bycooperative learning Think Pair Square (TPSq), while the control class given conventional learning.Based on the results of descriptive analysis, it showed that the developing of Cooperative Learning Think Pair Square (TPSq) produced good learning tools because it met: (1) both categories for the ability of teachers to manage learning, (2) active categories for student activities, (3) positive category for student responses and (4) meet the category of validity, reliability and sensitivity to THB. Based on the results of the descriptive analysis showed that the experimental phase of cooperative learning Think Pair Square (TPSq) effective based on several things, namely: (1) the ability of teachers to manage learningenvironmet, (2) the activity of students, (3) the response of students and (4) the completenessof learning outcomes. KEYWORD: software development, cooperative learning Think Pair Square (TPSq), and material cubes, blocks, prism, and pyramid